Os impactos do Programa de Modernização Integrada do Ministério da Fazenda no modelo de governança corporativo da instituição - Barbosa, Fernando Nascimento (2016)
This work addresses issues of governance focused on results in members of public organizations of direct administration of the Brazilian Federal Executive Branch. More specifically, we tried to make an analysis of the impact of intervention actions in governance and the brasilian Ministry of Finance undertaken in the period between the years 2011 and 2015, organized in the form of the Programa de Modernização Integrada do Ministério da Fazenda ( PMIMF), to understand whether those actions contributed to the construction of a more conducive organizational environment to coordination and joint actions between the agencies that integrate the ministry with a view to creating value for society and other stakeholders. This analysis considered the review of the literature on governance and the Theory of Public Policy Fragmentation (2003), Humberto Falcão Martins, on the grounds that the fragmentation of management policies creates inefficiency and undermines the generation of results for society and stakeholders. This discussion is established precisely from the development of a qualitative analytical model of governance in organizations, having as reference models Building Blocks (FONTES FILHO, 2013), Governança para Resultados na Administração Pública (MARTINS and MARINI, 2010) e Governança Pública: Referencial Básico de Governança Aplicável a Órgãos e Entidades da Administração Pública e Ações Indutoras de Melhoria (TCU, 2014) and the completion of a case study for the application of this model in the Ministry of Finance. The work considered then conducting bibliographic research, documentary research and case study. In addition, we interviewed a group of people in the ministry to raise their awareness on the issues under review. The conclusion is that the program has produced several impacts on the governance structure and the ministry governance practices and that these impacts have contributed to the reduction of fragmentation of management and to create an organizational environment where there is more coordination and joint actions between the agencies with a view to generating results for society and other stakeholders.